Simulation of the loss-cone instability in spherical systems – II. Dominating Keplerian potential. Issue 4 (17th January 2020) - Polyachenko, E V; Berczik, P; Just, A; Shukhman, I G
ABSTRACT: According to our previous theoretical findings, physical processes in centres of galaxies, star clusters, and the Oort comet cloud can be significantly altered by a new so-called 'gravitational loss-cone instability'. Using N -body simulations of a spherical stellar model in the dominating Keplerian potential, we confirm the possibility of the instability and go beyond the linear theory. Unlike most other instabilities, the new one shows no notable change in spherical geometry of the cluster, but it significantly accelerates the speed of diffusion of particles in phase space leading to a repopulation of the loss cone and early instability saturation.